2021
DOI: 10.1155/2021/7337988
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Anti‐Inflammatory Effects of Lactobacillus plantarum ZS62 on Alcohol‐Induced Subacute Hepatic Damage

Abstract: Lactobacillus plantarum ZS62 is a newly isolated strain from naturally fermented yogurt that might offer some beneficial effects in the setting of alcohol-induced subacute liver injury. The liver-protective effect of L. plantarum ZS62 was investigated by gavage feeding of mice with this Lactobacillus strain ( 1 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In the present study, we found that alcohol reduced the expression level of Nrf2 and SOD2 in mice, causing an imbalance in the redox system, while LP-cs reversed these effects ( Figures 5F–H ). Similar to our findings, a study found that L. plantarum ZS62 pretreatment appeared to confer hepatic protection on alcohol-induced subacute hepatic damage by enhancing antioxidative capacity ( Gan et al, 2021 ). In addition, oxidative stress is related to macromolecule damage and activation of several cell survival and death pathways.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we found that alcohol reduced the expression level of Nrf2 and SOD2 in mice, causing an imbalance in the redox system, while LP-cs reversed these effects ( Figures 5F–H ). Similar to our findings, a study found that L. plantarum ZS62 pretreatment appeared to confer hepatic protection on alcohol-induced subacute hepatic damage by enhancing antioxidative capacity ( Gan et al, 2021 ). In addition, oxidative stress is related to macromolecule damage and activation of several cell survival and death pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Alcohol causes oxidative stress in the hippocampus (Zhao et al, 2021). When the antioxidant defense system is turned on, Nrf2 activates the transcription of antioxidant genes such as SOD2 (Hoang et al, 2019;Durymanov et al, 2020).…”
Section: Lactobacillus Plantarum Culture Supernatants Alleviates Alco...mentioning
confidence: 99%
“…Long time Lactobacillus rhamnosus GG supplementation prevented alcohol-induced colonic dysbiosis [ 47 ]. Lactobacillus plantarum pretreatment relieved alcohol-induced subacute liver injury by reducing inflammation and enhancing antioxidative response of liver [ 48 , 49 ]. We found that Lactobacillus abundance was negatively correlated with the level of phenylalanine.…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholic beverages, which include distilled spirits, fermented spirits, and premixed spirits with an alcohol content of more than 0.5%, have long been consumed for social entertainment and leisure. 20 However, excessive alcohol consumption can cause a variety of health risks, including ALD, which is one of the most common liver diseases in the world. Therefore, the discoveries of bioactive components with potential to protect against acute alcoholic hepatic impairment and the development of rational prevention or treatment strategies have received increasing attention.…”
Section: ■ Discussionmentioning
confidence: 99%